THE POLITICAL LIFE OF THE PERIOD DURING WHICH KOMIL KHOREZMI WAS ACTIVE (TAMADDUN NURI JURNALI, 2025)
This article highlights the political life of the second half of the 19th century, during which the famous figure Komil Khorezmi an outstanding statesman of his time, a skilled translator, and a powerful poet who made an invaluable contribution to the development of Uzbek literature and music was active. His role during this period is also analyzed.